Adolescents with Developmental Dyscalculia Do Not Have a Generalized Magnitude Deficit – Processing of Discrete and Continuous Magnitudes - McCaskey, Ursina; von Aster, Michael; O’Gorman Tuura, Ruth; Kucian, Karin (Frontiers in Human Neuroscience, 2017)
The link between number and space has been discussed in the literature for some time, resulting in the theory that number, space and time might be part of a generalized magnitude system. To date, several behavioral and neuroimaging findings support the notion of a generalized magnitude system, although contradictory results showing a partial overlap or separate magnitude systems are also found. The possible existence of a generalized magnitude processing area leads to the question how children with developmental dyscalculia, known for deficits in numerical-arithmetical abilities, process magnitudes. By means of neuropsychological tests and functional magnetic resonance imaging we aimed to examine the relationship between number and space in typical and atypical development. Participants were 16 adolescents with developmental dyscalculia (14.1 years) and 14 typically developing peers (13.8 years). In the functional magnetic resonance imaging paradigm participants had to perform discrete (arrays of dots) and continuous magnitude (angles) comparisons as well as a mental rotation task. In the behavioral tests, adolescents with dyscalculia performed significantly worse in numerical and complex visuo-spatial tasks, but showed similar results when making discrete and continuous magnitude decisions. A conjunction analysis revealed commonly activated higher order visual (inferior and middle occipital gyrus) and parietal (inferior and superior parietal lobe) magnitude areas for the discrete and continuous magnitude tasks. Moreover, no differences were found when contrasting both magnitude processing conditions, favoring the possibility of a generalized magnitude system. Group comparisons further revealed that dyscalculic subjects showed increased activation in domain general regions, whilst typically developing peers activate task specific areas to a greater extent. In conclusion, our results point to the existence of a generalized magnitude system in the occipito-parietal stream in typical development. The detailed investigation of spatial and numerical magnitude abilities in developmental dyscalculia reveals that the deficits in number processing and arithmetic cannot be explained with a general magnitude deficiency. Our results further indicate that multiple neuro-cognitive components might contribute to the explanation of developmental dyscalculia.